Perlindungan Hukum Bagi Pasien dalam Pelayanan Kesehatan di Kabupaten Sabu Raijua - Dela Sari Day; Orpa G Manuain; Adrianus Djara Dima (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This study aims to find out and analyze legal protection for patients in health services in Sabu Raijua Regency. This research is an empirical research supported by an empirical legal approach using primary data in the form of interviews with related parties and secondary data in the form of literature books, research journals, laws and regulations, the internet, dictionaries of articles or newspapers. which was obtained using interview methods and document studies and processed and analyzed in several stages, namely editing, data systematization, verification and interpretation and analyzed in a qualitative descriptive manner. The results of the study show that (1) Legal protection for patients in health services in Sabu Raijua Regency is contained in Law Number 17 of 2023 concerning Health, Law Number 73 of 1958 concerning Criminal Law Regulations for All Regions of the Republic of Indonesia and Amending the Criminal Code (KUHP), Law Number 1 of 2023 concerning the Criminal Code (KUHP), Burgelijk wetboek voor innesie (Civil Code). (2) Implementation of Legal Protection for Patients in Health Services in Sabu Raijua Regency Although it has been protected, in reality there are still shortcomings, namely it has not been implemented.